Economic impact of tariff rate quotas and underfilling: The case of canned fruit exports from South Africa to the EU - Chiedza L. Muchopa (Economies, 2021)
Export trade provided for under tariff rate quotas (TRQs) is an important contributor to improving South Africa's export access to European markets. The performance of exporter-administered TRQs has not received much research attention in the context of the below par market access utilisation of a given opportunity. The present study analysed how the country performed in terms of utilising its TRQ for canned pears, apricots, and peaches provided by the European Union (EU) for the period 2010 to 2019. The permit allocation system for TRQs in South Africa is described for further understanding of aspects of the TRQ system likely to affect quota fill. Performance was assessed in terms of yearly quota utilisation rates as well as welfare measured in equivalent variation calculated in a computable general equilibrium (CGE) trade model. The analysis found that the canned fruit TRQ exhibited a fill rate average of 61% for the past 10 years (2010-2019) and 49% for the period 2015-2019, thus falling far short of the goal of achieving full market access availed by the EU within the protocols of liberalised trade. The welfare effects of trade liberalisation confirmed the underutilisation of the TRQ indicated by a welfare loss, considering the difference in gains of an underutilised quota (USD 2497) and a fully utilised quota (USD 2530). The study highlights the importance of full utilisation of preferences.
Keywords: 330; agriculture; fruit products; tariff rate quota; trade policy; TRQ administration; welfare